Women in the ancient world - Neils, Jenifer (London : The British Museum Press, 2011)
Summary: This attractive book takes a fresh look at the representation of women from the ancient world. Packed with illustrations, it includes striking images of sculpture, wall paintings, ceramics and mummy cases, engravings, silver and jewels, ranging from public art to domestic artefacts. The book portrays a variety of roles and activities of women across a range of ancient cultures. Through themes such as the idealwoman, marriage, childbirth and the family, dress and nudity, work, religion, priestesses and goddesses, theauthor highlights the diverse roles and preoccupations of women in the ancient world, often with surprising resonances for our time.
Real women: an introduction -- Female stereotypes -- Mothers and mourners -- Working women -- The body beautiful -- Women and religion -- Royal women.
Includes index.
Keywords: Women -- History -- To 500.; Women -- Social conditions; Women -- Social life and customs; Women in art; History, Ancient